1998
DOI: 10.1046/j.1537-2995.1998.38698326339.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to hepatitis E virus among several populations in Greece: increased prevalence in an hemodialysis unit

Abstract: This study demonstrated a high prevalence of anti-HEV in a separate hemodialysis unit, without an association with the known routes of transmission of blood-borne viruses. This observation suggests that a still-undefined intra-unit factor or other factors are associated with HEV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…In some cases, this occurs after only 3 to 4 months, which makes the diagnosis of hepatitis E virus infection extremely difficult, particularly if HEV RNA or IgM anti-HEV antibodies are not used (5,17). In addition, reports suggest that some people may not produce a detectable antibody response and that the prevalence of anti-HEV in areas where the disease is endemic is much lower than expected, at a rate of 2.8 to 20.2%, with a very high proportion of HAV-seropositive individuals (3,8). In industrialized countries, anti-HEV antibodies have regularly been found at a rate below 5%, and in Spain, a level of 1 to 3% is reported in blood donors (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, this occurs after only 3 to 4 months, which makes the diagnosis of hepatitis E virus infection extremely difficult, particularly if HEV RNA or IgM anti-HEV antibodies are not used (5,17). In addition, reports suggest that some people may not produce a detectable antibody response and that the prevalence of anti-HEV in areas where the disease is endemic is much lower than expected, at a rate of 2.8 to 20.2%, with a very high proportion of HAV-seropositive individuals (3,8). In industrialized countries, anti-HEV antibodies have regularly been found at a rate below 5%, and in Spain, a level of 1 to 3% is reported in blood donors (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a prevalence among hemodialyzed patients higher than that among blood donors or the general population (1,6). However, there are no conclusive studies for this transmission mechanism and it seems that the risk, if it exists, would be low (1,8,28).…”
mentioning
confidence: 99%
“…Military and logistic restrictions precluded our acquiring accurate clinical, socioeconomic, or census data amongst the refugee community who appeared to be most at risk for hepatitis, presumably because of poor living conditions. Displaced populations in other places (for example, Albanians in Greece, 32 Indochinese in Australia 33 ) have been shown to have higher rates of HEV antibodies than the native populations, and the risk of HEV to groups affected by natural disasters and wars is well recognised. 5,34 Previously, sporadic or epidemic hepatitis E had been recognized in northern and central African countries.…”
Section: Discussionmentioning
confidence: 99%
“…5%) had chronic liver disease. Although four EL2 seroepidemiological studies have also found that patients with comorbidities [5,[56][57][58] have a higher anti-HEV IgG positivity in comparison to the reference group a larger number of studies found no association (Table 6). This further supports the above-mentioned hypothesis that comorbidities affecting the liver are mainly associated with a higher risk of clinical disease but not infection.…”
Section: Comorbidity As a Risk Factormentioning
confidence: 98%
“…However, haemodialysis patients in four different studies [57,[96][97][98], those who had undergone minor surgery and abdominal surgery in Spain [4], healthcare workers in emergency admission and surgery in Germany [99] and male prisoners and drug treatment patients in Denmark [56] were found to have a higher anti-HEV IgG prevalence than the reference group.…”
Section: Potential For Parenteral Transmissionmentioning
confidence: 99%